Monte Carlo study of a small field of view YAlO3:Ce pinhole camera for imaging with Rb-82 by detection of bremsstrahlung X-rays. (5th August 2021) - Nakanishi, K.; Yamamoto, S.
Abstract: One of the applications of single-photon emission computed tomography (SPECT) and positron emission tomography (PET) is myocardial imaging. Myocardial perfusion imaging with PET (MPI-PET) is gradually becoming an alternative to MPI-SPECT due to its higher image quality. Although Rb-82 is the most common tracer for MPI-PET, Rb-82 emits high-energy positrons with a long stopping range, resulting in blurring of the spatial resolution of the PET image. Due to the limitations of spatial resolution, imaging of Rb-82 in mice has not been reported. In this study, we propose a new method to achieve higher resolution imaging of Rb-82 in small animals than possible with PET imaging by detecting bremsstrahlung X-rays emitted by the positrons, and we validated the feasibility of this method using Monte Carlo simulation. We simulated a small field of view (FOV) pinhole X-ray camera based on a thin YAlO3 :Ce (YAP(Ce)) plate and analyzed the basic performance of the simulated camera for bremsstrahlung X-rays. The spatial resolution of a 0.5 mm-thick YAP(Ce) plate-based camera with a 1.0 mm pinhole collimator was 2.6 mm full width at half maximum (FWHM) at a distance of 17.5 mm from the surface of the collimator. Furthermore, we simulated imaging of a mouse heart phantom filled with Rb-82 of 67 MBq per milliliter. We observed the shape of the phantom in the image for a 10 - 45 keV energy window in a simulated measurement time of 4 minutes. We conclude that imaging of high-energy positron emitters at a higher resolution than by PET imaging is possible through detection of the bremsstrahlung X-rays emitted from the positrons.